Health as a social value - Konstańczak, Stefan (Studia Ecologiae et Bioethicae, 2012)
The starting point of the article is the thesis that Hippocrates’ rule: “the health of an ill person is the highest right” is not only the main rule of the conduct of medical staff but also includes a defined method of evaluation. According to the author, the consequence of such evaluation is a detailed rule “Firstly, not to harm”. This rule has got a universal character and cannot only be restricted to medical staff. Healthcare is not the domain of doctors alone. It is everybody’s obligation, as it is to ensure that people don’t risk their own health or others’. In support of this approach, Władysław Tatarkiewicz’s considerations have been mentioned in the article, especially those that combine an individual sense of happiness with a state of health. In the end, the author refers to empirical research, which shows dependence on the state of health on and acquired lifestyle and points to the greater rationale of health prevention rather than institutional medical care.